Guiding Students' Autonomous Learning to Improve the Effectiveness of Chemistry Classroom Teaching - Jia , Jianhua (Journal of Education and Educational Technologies, 2023)
The "Implementation Opinions of the General Office of the State Council on Deepening the Reform of Innovation and Entrepreneurship Education in Higher Education Institutions" emphasized that carrying out innovation and entrepreneurship education is a reform and innovation of higher education methods and methods, and higher education should attach importance to cultivating college students' innovation ability, practical ability, and innovative spirit. Implementing innovation and entrepreneurship education is not a stopgap measure to alleviate the current employment pressure on graduates, but rather to cultivate the comprehensive quality level and innovative awareness and ability of college students to adapt to social development through innovation and entrepreneurship education. Countless successful examples of hard work and innovation from small to large, from weak to strong will encourage a new generation of college students to continue to innovate and create social wealth.